Motorcycle Consumer Protection in Indonesia: An Analysis of eSAF Frame Implementation on Honda Matic Motorcycles - Yustisio Mahendra; Winserly Tan; Rufinus H. Hutauruk (IHSA Institute, 2024)
This research examines the protection of motorcycle matic consumers in Indonesia through an analysis of the implementation of the eSAF frame on Honda automatic motorbikes. The design of this research is normative legal research. This research uses a case approach method and a statutory approach. The results of the study, first, analyze the relevance of the Consumer Protection Law to Honda matic motorcycle users in Indonesia highlighting the need for legal reform in the face of changing times. Second, according to Article 4 of the Consumer Protection Law, consumer rights involve aspects of comfort, security, and safety in using goods and/or services. In addition, consumers have the right to receive correct, clear, and honest information regarding the condition and guarantee of goods and/or services from business actors. Third, the Consumer Protection Law is present to provide protection to consumers, as well as encourage them to be more critical and courageous to demand their rights if they feel harmed by business actors